(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Internal Model Control (IMC) is the basis of a systematic program Q on the parameters of the concept and is based on the many modern control technology control system design. The present research work presents a novel control scheme for tuning PID controllers using Internal Model control with the filter time constant optimized using Bee colony Optimization technique. The robustness is measured by a two-block structured singular value, and the disturbance rejection is measured by the minimum singular value of the integral gain matrix. PID controllers are used widely in Industrial Processes. Criteria based on disturbance rejection and system robustness are proposed to assess the performance of PID controllers. Tuning of PID controllers is accomplished using Internal Model control scheme. In this paper, we propose an optimal filter design IMC IMC-PID controller for unstable process better set point tracking. IMC includes tuning of filter constant λ. The controller is suitable for different values of the filter tuning parameters to achieve the desired response in due IMC method is based on pole-zero offset, including IMC design principle method causes the response sets a good point. However, in a stable long lag time of load disturbances leading to undesirable process which is the result of the IMC control industry. Therefore, IMC has been a popular design process processing industry, especially as a means for adjusting the single-loop, PID controllers.